Giant Purulent Pericarditis with Cardiac Tamponade Due to Streptococcus intermedius Rapidly Progressing to Constriction - TİGEN, ELİF; SARI, İBRAHİM; AK, KORAY; TİGEN, MUSTAFA KÜRŞAT; KORTEN, VOLKAN (WILEY-BLACKWELL, 2015)
Purulent pericardial effusion, although rare, is a life-threatening condition usually produced by the extension of a nearby bacterial infection locus or by blood dissemination in the immune-suppressed subjects or in the course of cardiothoracic surgery. Because clinical features of purulent pericardial effusion are often nonspecific, it can cause delay in diagnosis. Therefore, a high index of suspicion is required for timely diagnosis and management. Herein, we describe a case of giant purulent pericardial effusion due to Streptococcus intermedius with the history of bronchiectasis and pneumonia, which was successfully treated with pericardiocentesis via parasternal approach, appropriate antibiotics, and pericardiectomy. Mini-Abstract Purulent pericardial effusion, although rare, is a life-threatening condition usually produced by the extension of a nearby bacterial infection locus or by blood dissemination in the immune-suppressed subjects or in the course of cardiothoracic surgery. Because clinical features of purulent pericardial effusion are often nonspecific, it can cause delay in diagnosis. Therefore, a high index of suspicion is required for timely diagnosis and management. Herein, we describe a case of giant purulent pericardial effusion due to Streptococcus intermedius with the history of bronchiectasis and pneumonia, which was successfully treated with pericardiocentesis via parasternal approach, appropriate antibiotics, and pericardiectomy.
Keywords: giant purulent pericarditis; pericardial effusion; tamponade; Streptococcus intermedius; constrictive pericarditis; MILLERI GROUP; PERICARDIOCENTESIS; ECHOCARDIOGRAPHY; CONSTELLATUS; MANAGEMENT; ANGINOSUS; ABSCESS